2016 Physics Education Research Conference Proceedings 2016
DOI: 10.1119/perc.2016.pr.008
|View full text |Cite
|
Sign up to set email alerts
|

Reading between the lines: lab reports help high school students develop abilities to identify and evaluate assumptions

Abstract: Most of the research surrounding development of scientific abilities among introductory physics students has been conducted at the college level. A shift in the high school science culture encouraged by NGSS has changed the focus of K-12 physics education making similar work necessary at the K-12 level This paper describes how high school students in a first-year physics course developed assumptionassociated abilities during the six months they studied mechanics. Using their written laboratory reports, we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Labs that implement the ISLE approach have been described in many publications [5,6,[26][27][28][29][30]. They differ from traditional labs and other reformed lab approaches [31,32] (d) When designing, conducting and communicating the results of the experiments, the students use scientific abilities rubrics [2] to guide and improve their work and the instructors use the same rubrics to assess and provide feedback to the students.…”
Section: Isle-approach Labs Using Apparatus or Videosmentioning
confidence: 99%
“…Labs that implement the ISLE approach have been described in many publications [5,6,[26][27][28][29][30]. They differ from traditional labs and other reformed lab approaches [31,32] (d) When designing, conducting and communicating the results of the experiments, the students use scientific abilities rubrics [2] to guide and improve their work and the instructors use the same rubrics to assess and provide feedback to the students.…”
Section: Isle-approach Labs Using Apparatus or Videosmentioning
confidence: 99%
“…As a result, students need repeated engagement with the abilities they are expected to develop. While studies conducted at the high school and college level found that students are capable of developing these scientific abilities [9,10], as researchers we are unaware of the long-term effects of learning physics through this approach for students. We need to know if the ISLE approach helps students learn how to develop the mindset necessary to reason independently and solve open-ended problems before starting their careers.…”
Section: Introductionmentioning
confidence: 99%